PENGARUH GREEN MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK AIR MINUM DALAM KEMASAN ADES PADA MAHASISWA UNIVERSITAS SLAMET RIYADI SURAKARTA - Mamahit, Lailia (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
The objective of this study are to know the effect of green marketing to purchasing decisions Ades. Population in this study were students in Slamet Riyadi University. In this research the large amount of samples was determined as many as 100 respondents. Technique analysis of data used was multiple linear regression technique analysis. The data used in this research are primary data obtained by giving questionnaires to respondents. Test precondition analysis used in this study include: normality, multicollinearity, heteroscedasticity autocorrelation and linearity hypothesis testing in this study using multiple regression analysis, F test, T test and the coefficient of determination. Based on the result of the study it can be concluded that the green product influence positive on purchasing decisions Ades, green price no influence on purchasing decisions Ades, green promotion influence positive on purchasing decisions Ades and green place influence positive on purchasing decision Ades. Based on the results of the calculation Adjusted R square of 0,325 so that it can be interpreted that 32,5 percent Ades purchasing decisions green marketing. Keywords: green marketing, marketing strategy, purchasing decisions.